Blockade of BK channels attenuates chronic visceral hypersensitivity in an IBS-like rat model. (August 2021) - Fan, F; Chen, Y; Chen, Z; Guan, L; Ye, Z; Tang, Y; Chen, A; Lin, C
Background: Visceral hypersensitivity in irritable bowel syndrome (IBS) is still poorly understood, despite that chronic abdominal pain is the most common symptoms in IBS patients. To study effects of BK channels on visceral hypersensitivity in IBS rats and the underlying mechanisms, IBS rats were established by colorectal distention (CRD) in postnatal rats. The expression of large-conductance calcium and voltage-dependent potassium ion channels (BK channels) of the thoracolumbar spinal cord was examined in IBS and control rats. The effects of BK channel blockade on visceral hypersensitivity were evaluated. The interaction of BK channels and N-methyl-D-aspartate acid (NMDA) receptors was explored, and synaptic transmission at superficial dorsal horn (SDH) neurons of the thoracolumbar spinal cord was recorded by whole-cell patch clamp in IBS rats. Results: The expression of the BK channels of the thoracolumbar spinal cord in IBS rats was significantly reduced. The blockade of BK channels could reduce the visceral hypersensitivity in IBS rats. There was an interaction between BK channels and NMDA receptors in the spinal cord. The frequency of spontaneous inhibitory postsynaptic currents (sIPSCs) in SDH neurons is significantly reduced in IBS rats. The blockade of BK channels depolarizes the inhibitory interneuron membrane and increases their excitability in IBS rats. Conclusions: BK channels could interact with NMDA receptors in the thoracolumbar spinal cord of rats and regulate visceral hypersensitivity in IBS rats.